1130 What Portable Home Sleep Tests and Holter Monitors Are Missing: An Unusual Case of Positional Bradycardia Detected on Polysomnogram. (27th April 2018) - Ramaniuk, Aliaksandr; Vaitkus, Linas; ,
Abstract: Introduction: The effects of supine, left lateral decubitus (LLD), and right lateral decubitus (RLD) positions on cardiovascular and autonomic activity have long been recognized. Decubitus positioning has been shown to increase vagal enhancement in recovery positioning following cardiac resuscitation, to reduce myocardial oxygen consumption, and to decrease probability of ventricular arrhythmias. This case demonstrates the unique utility of polysomnography (PSG) in assessing positional influences during unexplained bradyarrhythmic episodes, and stresses the importance of increasing the recognition of PSG's value outside of sleep specialists and sleep disordered breathing assessments. Report of Case: A 60-year-old male with past medical history of coronary artery disease presented for sleep evaluation and CPAP titration. Medications include aspirin 81mg, metoprolol 24 mg daily, clopidogrel 75 mg daily, isosorbide mononitrate ER 30 mg daily. During overnight PSG recording, total sleep time -391 minutes, AHI - 20, and lowest SaO2 - 86.9%. Patient's resting heart rate (HR) was 62 at time of lights out, remaining in range of 60–67 while in RLD position. Bradycardia was noted with sudden decrease to HR of 48, immediately following positional change to LLD. Patient's PSG shows clear, recurrent association between positional change, specifically LLD position and profound bradycardia. This association would not be identified by continuous cardiac monitoring or home sleep testing. Conclusion: The specific mechanisms and influences of recumbent positions on the autonomic nervous system are currently being debated. One recent explanation of LLD positional bradycardia was attributed to echocardiographically confirmed decrease in the diameter and area of the inferior vena cava, resulting in increased flow and reflexive bradycardia. (Sazaki J. Exp. Med., 2017) The case demonstrates that PSG is exclusive in its comprehensive assessment capacity and in the ability to present complex and under-recognized physiologic associations to the clinician.